A Guide to Performing Cardiac Surgery in Patients with Hereditary Bleeding Disorders. Issue 1 (27th October 2014) - Bhave, Prachi; McGiffin, David; Shaw, James; Walsh, Megan; McCarthy, Penny; Tran, Huyen; Davis, Amanda Katherine
Abstract Background and Aim This study presents the experience of a large Australian hospital in performing cardiac surgery on patients with hereditary bleeding disorders (HBDs) and provides a suggested approach for their perioperative management. Methods Medical records of patients with HBDs who underwent cardiac surgery from January 1997 to December 2013 were reviewed. Results Seventeen patients were included in this study, 13 with Hemophilia A, one symptomatic Hemophilia A carrier, one with Hemophilia B, and two with von Willebrand Disease. Cardiac surgical procedures performed included 10 coronary artery bypass graft (CABG) operations, two aortic valve replacements, two mitral valve repairs, two aortic root replacements, and one combined aortic valve replacement and CABG. Perioperative management centered on factor substitution to maintain normal factor levels. Perioperative outcomes including length of hospital stay, mortality, and return to the operating room for bleeding were recorded. Two patients returned to the operating room for bleeding, one patient on the first postoperative day and one patient at day 20 postoperatively with pericardial bleeding. Conclusions Most patients demonstrated excellent hemostasis, suggesting that cardiopulmonary bypass surgery in HBD patients may be safely performed with careful planning. doi: 10.1111/jocs.12464 (J Card Surg 2015;30:61–69)